Catalytic oxidation of aromatic hydrocarbons by a molecular iron–NHC complex. Issue 9 (11th April 2017) - Lindhorst, Anja C.; Schütz, Jan; Netscher, Thomas; Bonrath, Werner; Kühn, Fritz E.
Abstract : An iron–NHC complex bearing a tetradentate bis(N-heterocyclic carbene) ligand is applied as catalyst for the oxidation of methyl substituted arene substrates. Abstract : An iron–NHC complex bearing a tetradentate bis(N-heterocyclic carbene) ligand is applied as catalyst for the oxidation of methyl substituted arene substrates. Using hydrogen peroxide as the oxidant p -xylene and pseudocumene are converted to the corresponding phenols and benzoquinones. The influence of various reaction parameters like temperature, catalyst loading, and oxidant concentration is investigated and kinetic experiments reveal that a temperature reduction leads to an increased catalyst lifetime. Furthermore, an interesting selectivity towards unexpected phenolic products resulting from a methyl shift reaction is observed.